FAKTOR - FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI GOING CONCERN DIPERUSAHAAN PERTAMBANGAN 2016 - 2019 - hansen hanly (Fakultas Ekonomi Prodi Akuntansi, 2020)
The purpose of this research is to analyze and test whether audit lag, solvability, opinion shopping, audit opinion on the previous year, and reputation of accounting public office affect the going concern audit opinion acceptance of mining sector company that listed in Indonesia Stock Exchange period 2016 – 2019. The type of research we used is quantitative descriptive research. The research sample that has been selected is 41 companies with observating 164 data that obtained through purposive sampling technique with certain criteria. Hypothesis testing and data analysis techniques are obtained by SPSS 20 with logistic regression method. The results of the study simultaneously show that audit lag, solvability, opinion shopping, audit opinion on the previous year, and reputation of accounting public office do not have significant influence on going concern audit opinion acceptance of mining sector company that listed in Indonesia Stock Exchange period 2016 – 2019.